Blockchain-based Decentralized Application for Electronic Voting Using an Electronic ID - Monteiro, José Diogo (2020)
In this work, we present a decentralized and self-tallying electronic voting protocol that substantially enhances the privacy of voters and diminishes centralization. ese properties are accomplished through a symbiotic relationship between the Ethereum Blockchain and the Portuguese electronic ID. Unlike previously proposed Blockchain e-voting protocols, this is the rst implementation that more closely ful lls most of the security requirements of a real-world voting scheme. Furthermore, our system improves currently in-use e-Voting systems by using a self-tallying protocol. us, each voting citizen is able to compute the election tally and has complete control over their own vote. e execution of this protocol is enforced using the consensus mechanism that safeguards the Ethereum Blockchain. To prove its feasibility, we tested the implementation on the o cial PoW (Proof of Work) test network of Ethereum (Ropsten). e - nancial and computational breakdowns are on par with the leading Blockchain e-voting protocol.